THE INFLUENCE OF WORD OF MOUTH, PRICE AND BRAND IMAGE ON PATIENTS' DECISION TO USE SERVICES IN PRACTICE MIDWIFE DEBY - Syi Syi Liani; Dewi Shinta Wulandari (Jurnal Ekonomi, 2023)
This study aims to determine whether the patient's decision at midwife Deby's practice is influenced by word of mouth, price and brand image. The sample for this study was 240 respondents. Sampling using random sampling is sampling that provides equal opportunity for each member of the population to be sampled. using multiple regression tests to analyze the data and the coefficient of determination (R2) to assess the hypothesis, partial test (t test), and simultaneous test (F test), while data processing using SPSS 22. The results showed that partially word of mouth, price and brand image influences patient's decision to use services at Deby's midwife practice, and simultaneously word of mouth, price and brand image influences patient's decision to use services at Deby's midwife practice